Die sprechende Stadt. Stadtumbau in Paderborn um 1600 und in der Gegenwart - Süßmann, Johannes

Einführung - Eybl, Franz M.; Fulda, Daniel; Süßmann, Johannes (Bündnisse. Politische, soziale und intellektuelle Allianzen im Jahrhundert der Aufklärung)

Bündnisse. Politische, soziale und intellektuelle Allianzen im Jahrhundert der Aufklärung

Das Mainufer von Aschaffenburg: Romantische Geschichtsinszenierung und Herrschaftslegitimation - Süßmann, Johannes (Kolossale Miniaturen. Festschrift für Gerrit Walther)
Keywords: Aschaffenburg Ludwig I. König von Bayern Gartenkunst Main Residenzschloß Villen Gärtner; Friedrich von Antikenrezeption Museen Herrschaftslegitimation Bildungsbürger

Blow your Trumpets Gabriel« – Der Heavy Metal und die Frage des Satanismus - Hansen, Christin (Kirchliche Zeitgeschichte)

Vernünftige Deutsche, chaotische Griechen? Stereotype und historisches Lernen - Hansen, Christin; Pleitner, Berit (Geschichte lernen)

Steuermoral in Westdeutschland nach dem Zweiten Weltkrieg. Eine diskursanalytische Rekonstruktion - Schönhärl, Korinna (Leviathan)
Die Klage über mangelnde Steuermoral ist in der aktuellen Medienberichterstattung omnipräsent, aber sie ist nicht neu: Bereits kurz nach dem Zweiten Weltkrieg wurde bemängelt, die Deutschen in den westlichen Besatzungszonen hinterzögen ihre Steuern. Verfiel die westdeutsche Steuermoral schon damals? Wie veränderte sie sich im Zeitraum zwischen 1945 und 1953? Nach einem kurzen Überblick über die Geschichte der interdisziplinären Steuermoralforschung und einigen methodischen Überlegungen, wie Historiker*innen die Entwicklung der Steuermoral qualitativ untersuchen können, wird im vorliegenden Aufsatz der Diskurs um das Steuerzahlen in der Nachkriegszeit analysiert. Durch die Analyse von Zeitungsberichten und Parlamentsdebatten werden drei unterschiedliche, konkurrierende Narrative identifiziert, die geeignet waren, ganz verschiedene »policy windows« zu öffnen. Die historische Untersuchung zeigt, dass Narrative über das (ehrliche) Steuerzahlen immer mit bestimmten politischen Interessen verknüpft sind - und dass sie deshalb auch im aktuellen Diskurs über das (ehrliche) Steuerzahlen sorgfältig analysiert werden sollten.
Keywords: Political Science and International Relations; Linguistics and Language; Sociology and Political Science; Language and Linguistics

Socially Responsible Investment in 19th Century Greece: A Case Study of a Swiss Banker - Schönhärl, Korinna (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Altruistically motivated investment has become the subject of economic, psychological and sociological research in recent years. The long tradition of ethical considerations concerning investment behavior has often been mentioned by historians but rarely investigated. This paper presents a case study of the 19th century philhellene banker Jean-Gabriel Eynard, who was philanthropically active in Greece, but also invested part of his capital on the emerging Greek market. Drawing on the methodological approach of the “sociology of morality”, this article examines how Eynard invested in Greece, which norms and values concerning investment behavior he articulated and how far they were comparable with the norms and values of today’s Socially Responsible Investment. What emerges is that the practices and the norms of Socially Responsible and Ethical Investment then and now are remarkably similar, while the “moral background” (G. Abend) has changed considerably in some, but not all points.
Keywords: Economics; Econometrics and Finance (miscellaneous); Sociology and Political Science; History; Cultural Studies

The full range of leadership. Welche Zusammenhänge gibt es zwischen Führungsverhalten und schulischen Qualitätsindikatoren? - Bloh, Bea; van Ophyusen, Stefanie (Schulmanagement)

Forschendes Lernen in der Lehrerausbildung – Gestaltung und Erforschung des Praxissemesters - Bloh, Bea; Behrmann, Lars; Homt, Martina; van Ophuysen, Stefanie (Herausforderung Kohärenz: Praxisphasen in der universitären Lehrerbildung. Bildungswissenschaftliche und fachdidaktische Perspektiven)

Aural Worldmaking: An Introduction - Mildorf, Jarmila (CounterText)

The Irrelevance of Relevance Theory for the Study of Generic Fiction - Mildorf, Jarmila (Style)

Can Sounds Narrate? Prosody in Sound Poetry Performance - Mildorf, Jarmila (CounterText)

Ressourcenorientiertes Schreiben. Tagebücher, Skizzen und Notate in der sozio-therapeutischen Praxis. Mit einem Exkurs zum Tagebuch der Trauer von Roland Barthes - Mildorf, Jarmila; Ketteler, Daniel (Jahrbuch Literatur und Medizin)

Why Poetry Matters: Defamiliarization and Perspective in Poetry - Mildorf, Jarmila (Lyrik und Medizin)

„Der Imperativ des Nassauerns, Durchmogelns und Absahnens“: Debatten um Steuermoral in der BRD Anfang der 1980er Jahren - Schönhärl, Korinna (Geschichte in Wissenschaft und Unterricht)

Geld zurück! Internationale Finanzkontrolle in Griechenland im 19. Jahrhundert und in der Gegenwart - Schönhärl, Korinna (Grenzüberschreitende institutionalisierte Zusammenarbeit von der Antike bis zur Gegenwart)

Die Steuermoral weltweit. Eine Artikelserie in der Frankfurter Allgemeinen Zeitung in den Jahren 1963/64 - Schönhärl, Korinna (Moderner Kapitalismus. Wirtschafts- und unternehmenshistorische Beiträge)

"I don't see why I would ever want to use it": Analyzing the Usability of Popular Smartphone Password Managers - Seiler-Hwang, Sunyoung; Arias Cabarcos, Patricia; Marín, Andrés; Almenáres, Florina; Díaz Sánchez, Daniel; Becker, Christian (Proceedings of the 2019 ACM SIGSAC Conference on Computer and Communications Security, CCS 2019, London, UK, November 11-15, 2019)

Poster: Towards a Framework for Assessing Vulnerabilities of Brainwave Authentication Systems - Becker, Karen; Arias Cabarcos, Patricia; Habrich, Thilo; Becker, Christian (Proceedings of the 2019 ACM SIGSAC Conference on Computer and Communications Security, CCS 2019, London, UK, November 11-15, 2019)

A Survey on Adaptive Authentication - Arias Cabarcos, Patricia; Krupitzer, Christian; Becker, Christian (ACM Comput. Surv.)

Narrating Selves and the Literary from the Bible to Social Media (Partial Answers)

Aural Worldmaking: Audionarratological Approaches to Sound and Narrative (CounterText)

Dance, Text and Philosophy in Gertrude Stein’s ‘One Dancing’ and Roger Scruton’s Perictione in Colophon - Mildorf, Jarmila (Germanisch-Romanische Monatsschrift)

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Autobiography, the Literary and the Everyday in Paul Auster's 'Report from the Interior' - Mildorf, Jarmila (Partial Answers)

Konzeptionelle, strukturelle und inhaltliche Gestaltungsaspekte des Praxissemesters an der Universität Paderborn - Herzig, Bardo; Wiethoff, Christoph (Praxissemester (Religion) in NRW: Bilanz und Perspektiven)

Symmetry and motion primitives in model predictive control - Flaßkamp, Kathrin; Ober-Blöbaum, Sina; Worthmann, Karl (MCSS)

Implikationen der digitalen Transformation für die didaktische Arbeit des betrieblichen Ausbildungspersonals - Gössling, Bernd; Hagemeier, Daniel; Janssen, Elmar; Sloane, Peter F. E. (Jahrestagung der DGfE-Sektion Berufs- und Wirtschaftspädagogik)

Berufsbildung 4.0 als didaktische Herausforderung : zum Umgang von Lehrkräften an berufsbildenden Schulen mit digitalisierten Arbeitswelten - Gössling, Bernd; Hagemeier, Daniel; Sloane, Peter F. E. (Zeitschrift für Berufs- und Wirtschaftspädagogik)

TLS/PKI Challenges and Certificate Pinning Techniques for IoT and M2M Secure Communications - Díaz Sánchez, Daniel; Marín López, Andrés; Almenárez Mendoza, Florina; Arias Cabarcos, Patricia; Simon Sherratt, R. (IEEE Commun. Surv. Tutorials)

DNS/DANE Collision-Based Distributed and Dynamic Authentication for Microservices in IoT - Díaz Sánchez, Daniel; Marín López, Andrés; Almenárez Mendoza, Florina; Arias Cabarcos, Patricia (Sensors)

Octave-Band Microwave Frequency Synthesizer Using Mode-Locked Laser as a Reference - Bahmanian, Meysam; Tiedau, Johannes; Silberhorn, Christine; Scheytt, Christoph (2019 International Topical Meeting on Microwave Photonics (MWP))
An octave-band voltage-controlled oscillator is phase-locked on the envelope of the pulse train from a mode-locked laser. The locking scheme employs a balanced Mach-Zehnder modulator with two photodiodes as a phase detector. The phase.locked loop has a loop bandwidth of approximately 1MHz and an in-band phase noise of approximately -135dBc/Hz at all frequencies. The integrated jitter from 1kHz to 100MHz is 21fs, 18.3fs and 13.8fs at 5.016GHz, 7.6GHz and 10.032GHz carrier frequencies, respectively. To the authors' knowledge, this is the best jitter performance reported for a PLL with MZM-based phase detection and the first reported PLL of this type featuring an octave-band frequency range.

Die Auswirkungen der Digitalisierung auf die Bedeutung beruflicher Qualifikation aus betrieblicher Sicht - Harteis, Christian; Goller, Michael; Fischer, Christoph (Beruf, Beruflichkeit, Employability)

Becoming a Nurse Aide: An Investigation of an Existing Workplace Curriculum in a Nursing Home - Goller, Michael; Steffen, Bianca; Harteis, Christian (Vocations and Learning)

Assessment of Flexibilisation Potential by Changing Energy Sources Using Monte Carlo Simulation - Dunkelberg, Heiko; Sondermann, Maximilian; Meschede, Henning; Hesselbach, Jens (Energies)
In the fight against anthropogenic climate change, the benefit of the integration of fluctuating renewable energies (wind and photovoltaics) into the electricity grid is a widely proved concept. At the same time, a fluctuating and decentralised supply of energy, especially at lower voltage levels, leads to a local discrepancy in the power balance between generation and consumption. A possible solution in connection with demand side management is the grid-oriented flexibilisation of energy demand. The present study shows how the use of an innovative hybrid-redundant high-temperature heat system (combined heat and power (CHP), power-to-heat system (PtH), gas boiler) can contribute to a flexibilisation of the electrical energy demand of plastics processing companies. In this context, the flexibilisation potential of a company is to be understood as the grid-related change of the energy supply through a change of the energy sources within the framework of the process heat supply. For this purpose, an omniscient control algorithm is developed that specifies the schedule of the individual system components. A sensitivity analysis is used to test the functionality of the control algorithm. Determination of the electrical flexibilisation potential is carried out via a comprehensive simulation study using Monte Carlo methods. For this purpose, the residual load curves of four characteristic distribution grids with a high share of renewable energies as well as heat load profiles of injection moulding machines are taken into consideration. A frequency distribution provides information on the electrical flexibilisation potential to be expected depending on the various combinations. The evaluation is carried out using a specially introduced logic, which identifies grid-relevant changes in the company's power consumption as flexibilisation potential based on a reference load curve. The results show that a reliable energy supply for production is possible despite flexibilisation. Depending on the grid under consideration, there are differences in the exploitation of the potential, which essentially depends on the installed renewable capacity. Depending on the scenario under consideration, an average of up to 1486 kWhel can be shifted in a positive direction and 1199 kWhel in a negative direction.

On the impact of probabilistic weather data on the economically optimal design of renewable energy systems – a case study on La Gomera island - Meschede, Henning; Hesselbach, Jens; Child, Michael; Breyer, Christian (International Journal of Sustainable Energy Planning and Management)
Renewable energy and storage systems are widely discussed to minimise the impact of global warming. In addition to the temporal resolution of simulation tools, also the chosen input data might have a strong impact on the performance of renewable energy systems, and energy storage systems in particular. This study analyses the impact of probabilistic weather data on the design of renewable energy systems. The main objective is hereby the determination of the robustness of a recently state-of-the-art design process of a 100% renewable energy and storage system with varying probabilistic input data. The island of La Gomera, Canary Islands, is taken as a case study. Although all analysed systems show some variance in their results, the combination of vehicle-to-grid and power-to-hydrogen shows the best economic performance. Hereby, small island energy systems depending heavily on wind energy show higher variations than those with high shares of solar energy. This analysis illustrates clearly that the choice of one historical reference year is not suitable to determine the expected performance of an energy system. To learn about their sensitivity, synthetic probabilistic inputs as applied in this study are a good way to determine both the expected mean values and their variance.

Classification and clustering of the German plastic industry with a special focus on the implementation of low and high temperature waste heat - Dunkelberg, Heiko; Schlosser, Florian; Veitengruber, Frank; Meschede, Henning; Heidrich, Tobias (Journal of Cleaner Production)

On the transferability of smart energy systems on off-grid islands using cluster analysis – A case study for the Philippine archipelago - Meschede, Henning; Esparcia, Eugene A.; Holzapfel, Peter; Bertheau, Paul; Ang, Rosario C.; Blanco, Ariel C.; Ocon, Joey D. (Applied Energy)

Automatic Time Series Segmentation as the Basis for Unsupervised, Non-Intrusive Load Monitoring of Machine Tools - Seevers, J-P.; Johst, J.; Weiß, T.; Meschede, Henning; Hesselbach, J. (Procedia CIRP)

Increased utilisation of renewable energies through demand response in the water supply sector – A case study - Meschede, Henning (Energy)

Unraveling the Search Space of Abusive Language in Wikipedia with Dynamic Lexicon Acquisition - Chen, Wei-Fan; Al-Khatib, Khalid; Hagen, Matthias; Wachsmuth, Henning; Stein, Benno (Proceedings of the Second Workshop on Natural Language Processing for Internet Freedom)

Profile der Gegenwartsliteratur (Herausgebertätigkeit von Norbert Otto Eke ab Bd. 1, 2019)
Bd. 1: Michael Hofmann, Klaus von Stosch und Swen Schulte Eickholt. Würzburg 2019. 271 S.

A Hybrid Space Compactor for Adaptive X-Handling - Maaz, Mohammad Urf; Sprenger, Alexander; Hellebrand, Sybille (50th IEEE International Test Conference (ITC))
The test for small delay faults is of major importance for predicting potential early life failures or wearout problems. Typically, a faster-than-at-speed test (FAST) with sev¬eral different frequencies is used to detect also hidden small delays, which can only be propagated over short paths. But then the outputs at the end of long paths may no longer reach their stable values at the nominal observation time and must be considered as unknown (X-values). Thus, test response compaction for FAST must be extremely flexible to cope with high X-rates, which also vary with the test frequencies. Stochastic compaction introduced by Mitra et al. is controlled by weighted pseudo-random signals allowing for easy adaptation to varying conditions. As demonstrated in previous work, the pseudo-random control can be optimized for high fault efficiency or X-reduction, but a given target in fault efficiency cannot be guaranteed. To close this gap, a hybrid space compactor is introduced in this paper. It is based on the observation that many faults are lost in the compaction of relatively few critical test patterns. For these critical patterns a deterministic compaction phase is added to the test, where the existing compactor structure is re-used, but controlled by specifically determined control vectors.
Keywords: Faster-than-at-speed test; BIST; DFT; Test response compaction; Stochastic compactor; X-handling

Wärmeübertragung in Mikrokanälen zur Anwendung in neuartigen Wärmemotoren - Mügge, Nils; Kenig, Eugeny (Wärmeübertragung mit Phasenwechsel in fluiden Systemen: Ein Update)

Wärmegetriebene Motoren - Glouchenkov, Maxim; Kronberg, Alexander; Kenig, Eugeny; Mügge, Nils (CITplus)

Rauschen, Klang und Stille. Zur Musikalität von Literatur am Beispiel von Rilkes Malte Laurids Brigge. - van Laak, Lothar (Rilkes Musikalität)

„Profile der Gegenwartsliteratur“

Literarische Institutionen (Reihe: Grundthemen der Literaturwissenschaft)

"In erster Linie Kopfsache"!? ‒ Einstellungen zu schulischer Inklusion von Lehrkräften und Lehramtsstudierenden: Theoretische Grundlagen und jüngere empirische Befunde - Kullmann, Harry; Hülshoff, Andreas (Zwischen Persönlichkeitsbildung und Leistungsentwicklung. Fachspezifische Zugänge zu inklusivem Unterricht im interdisziplinären Diskurs)